Service providers’ perspectives and reproductive (in)justice among Roma women: a qualitative study in Spain - María Félix Rodríguez-Camacho; María José Sanchís-Ramón; Gaby Ortiz Barreda; Diana Gil-González (Sexual and Reproductive Health Matters)
The main objective of this study is to identify the barriers that prevent Roma women and girls from accessing reproductive rights derived from reproductive justice by analysing the discourses of service providers as a facilitating source of information. A qualitative study including nine semi-structured in-person interviews with community service providers was conducted in April-June 2019. The interview script addressed intercultural competences, views on gender discrimination against Roma women, resources available to fight against this discrimination, knowledge and use of these resources in reproductive justice, as well as the networks of actors involved. The qualitative analysis involved a discourse analysis. In the analysis, three focal areas were defined around which barriers to access spaces inspired by reproductive justice for Roma women could be identified. In each of the focal areas (stereotypes, discrimination and intercultural competences), discourses and practices have been observed in contrasting ways that can prevent access, as well as others that can facilitate access based on prejudices about Roma culture and people. The relationship models between professionals and users of the Roma population project stereotypes that are an obstacle in terms of accessing reproductive justice. The right of Roma women to preserve their culture and to actively participate in policies that affect them is not included and guaranteed in public policies. The intention to include the Roma population’s situation in an inclusive narrative exists, although without short-term effects. Reproductive justice is an absent framework within professional intervention and the institutional system. DOI: 10.1080/26410397.2024.2439661